Pengembangan Modul Pembelajaran Ips Berbasis Kearifan Lokal Uma Lengge Untuk Meningkatkan Literasi Budaya Siswa Sekolah Dasar - Runi Hartati; Rusmawan Rusmawan (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
This research is motivated by the need for a local wisdom Uma Lengge social studies learning module that can improve Cultural Literacy for fifth grade elementary school students. This article was written with the aim of developing a local wisdom Uma Lengge-based social studies learning module to improve Cultural Literacy for fifth grade elementary school students. The type of research used in this study is Research and Development (R&D). The research was conducted involving three validators, two elementary school teachers for needs analysis, and 23 students who were subjects in the trial process of the local wisdom Uma Lengge-based social studies learning module to improve Cultural Literacy. Observation, interviews and document studies are data collection techniques used in the study. Data analysis uses quantitative analysis and qualitative analysis. The results of the study are (1) The ADDIE development model is used in the development of a local wisdom Uma Lengge-based social studies learning module to improve Cultural Literacy for fifth grade elementary school students. (2) The quality of the IPS module with a Likert scale of 1-4 is included in the criteria of